THE EFFECTIVENESS OF SOCIAL MEDIA MARKETING ON B2C CUSTOMER LOYALTY: THE ROLE OF TRUST AND SERVICE QUALITY AS INTERVENING VARIABLES AT PT. BRI FINANCE - Amelia, Rodhiah Rizki; Qomariyah , Nurul; Hermawan, Haris (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to address the gap in previous research that focuses on social media marketing towards B2C customer loyalty through the role of trust and service quality. Method: This study uses quantitative research. The sampling technique used in this study is the non-probability sampling technique, namely purposive sampling. The sample used in this study was 100 respondents who had made repeat purchases and new customers at PT BRI Finance. The data was processed using SmartPLS 4.0. Results: The results of this study indicate that social media marketing towards customer loyalty is not significant with a p-value of 0.092 > 0.05. However, social media marketing has a positive effect on service quality with a p-value of 0.00 < 0.05, and it also has a positive effect on trust with a p-value of 0.00 < 0.05. Meanwhile, service quality does not have a significant effect on customer loyalty with a p-value of 0.163 > 0.05, and trust also does not have a positive effect on customer loyalty with a p-value of 0.085 > 0.05. Furthermore, social media marketing on customer loyalty through trust does not have a significant effect with a p-value of 0.087 > 0.05, and social media marketing on customer loyalty through service quality also does not have a significant effect with a p-value of 0.143 > 0.05. Novelty: This study highlights the limited direct impact of social media marketing on customer loyalty and the mediating role of trust and service quality, contributing to a deeper understanding of the relationship between digital marketing strategies and consumer behavior in the B2C sector.